Effective n = 1 action from orbifold compactification - Arianto,; Zen, F.P.; Gunara, B.E.; Zainuddin, Hishamuddin (2005)
We investigate the five dimensional N = 2 supergravity and its compactification to four dimensional theory. The five dimensional ungauged N = 2 supergravity coupled to vector- and hypermultiplets. In the model, the vector multiplets scalar manifold is arbitrary while the hypermultiplet scalars contain a generalized self dual Einstein manifold constructed by Calderbank and Pedersen and a universal hypermultiplet. The bosonic sectors of the low energy effective N = 1 supergravity in four dimensions is derived.